Perspective: Fröhner’s 1998 Posture Index For Lumbo-Pelvic Hip Complex - Kahraman, Yeliz (International Journal of Sport Studies for Health, 2024)
Objective: Lumbopelvic-hip complex enable to indicate force energy generation containing muscle proximal and distal end group connect abdomen and proximal low syndrome to losses of segment kinetic chain.Methods and Materials: Rarely postural segment distortion collapses complex movement sporting events after loading stress, accordingly dynamic postural strategies reactivate spinal balance were invesitageted. Uncommon lumbopelvic hip complex evaluation is detect to young and adult individuals using Fröhner’s posture index, according to specific complex syndrome provable review were examined. Fındings: The mechanic syndrome have been explained on compartment complex to be imbalanced musculature and myofascial dystrophy. Fröhner's posture index was explained with this perspective.Conclusion: A new approach to the evaluation of the lumbopelvic hip complex is postural medicine research.Keywords:  Posture index, lumbopelvic hip complex, syndrome